Retaining Social Workers: The Role of Quality of Work and Psychosocial Safety Climate for Work Engagement, Job Satisfaction, and Organizational Commitment. Issue 1 (1st January 2019) - Geisler, Martin; Berthelsen, Hanne; Muhonen, Tuija
ABSTRACT: The present study investigated how psychosocial safety climate (PSC), job demands (role conflict and work-family conflict), job resources (social support from superiors and social community at work), and assessments for quality of work relate to social workers' work engagement, job satisfaction, and organizational commitment. The results of the questionnaire study ( N = 831) showed that quality of work was strongly related to all three outcomes, whereas PSC was found to be related to social workers' job satisfaction. The contribution of the study is discussed in relation to understanding the retention of social workers.